Perfluoroisobutene: Poisonous choking gas - Patočka, Jiří (Univerzita obrany, Fakulta vojenského zdravotnictví, 2019)
Perfluoroisobutene (PFIB) is a colorless toxic gas which can be absorbed into the body by inhalation. The substance irritates the respiratory tract and may be used as a potential chemical warfare agent. Inhalation exposure may cause severe symptoms of pulmonary edema associated with wheezing, difficulty in breathing and sputum expectoration. A bluish skin color is also observed. Initially, cough and chest pain may occur. However, severe symptoms of pulmonary edema may be delayed for several hours before a rapid deterioration of health occurs. Excessive exposure may cause death.
Keywords: Acute lung injury; Chemical warfare agentIrritant gas; Perfluoroisobutene; PFIB; Toxicology